Management of hot flushes in UK breast cancer patients: clinician and patient perspectives. (2nd October 2017) - Fenlon, Deborah; Morgan, Adrienne; Khambaita, Priya; Mistry, Pankaj; Dunn, Janet; Ah-See, Mei-Lin; Pennery, Emma; Hunter, Myra S.; ,
Abstract: Introduction: Menopausal problems are among the most prevalent and distressing problems following breast cancer treatment, with 70% women experiencing hot flushes and night sweats (HFNS). A working party was set up to support the development of new research into the management of these problems. Methods: We conducted surveys to explore the need as perceived by women with breast cancer and establish current UK management practices. A patient survey was conducted through a charity, Breast Cancer Care, and a health professional survey via the UK Breast Intergroup. The HFNS Problem Rating Scale was used, as well as specific questions addressing the aims of the study. Results: Six hundred and sixty-five patients responded and 185 health professionals. Twenty-eight percent women had considered stopping adjuvant endocrine treatment because of HFNS, yet 34% had never been asked about HFNS by any health professional. The most commonly offered interventions were SSRIs, such as venlafaxine, yet only 25% patients had been offered these drugs. Cognitive behavioural therapy was rarely suggested (2%) despite good evidence. Discussion: This study shows a lack of coherence in the management of HFNS in breast cancer survivors, which may lead to reduced adherence to adjuvant therapy. There is an urgent need to develop guidelines to support management of HFNS after breast cancer.